PREVALENSI SEROPOSITIF HOG CHOLERA PASCAVAKSINASI PADA BABI DI KABUPATEN KARANGANYAR - , AMALLIA HERAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hog cholera or classical swine fever is a highly contagius viral desease of pig. This research was conducted to find out the prevalence seropositive of hog cholera in pig in Karanganyar and identify risk factor. Three hundred and eighty six blood samples were taken from 14 farms in Karanganyar. Sampling technics were applied in the research were multistage random sampling and simple at farm level. Risk information were obtained by interview to the farmers. Laboratory diagnosis was done by Enzyme Linked Immunosorbent Assay (ELISA). Data were analized by descriptive statistic, the association between hog cholera and risk factors were done by bivariate analysis base on chisquare ( ), and odds ratio (OR). Seroprevalence of hog cholera post vaccination in Karanganyar was 65,3%. Risk factors associated with hog cholera seropositive were trained farmer, vaccination procedure knowledge, duration of last vaccination, farm management type, sanitasi subtance, marriage system, sudden death in the last three months. Postvaccination immunity of hog cholera in pig farms in Karanganyar were good enough but should be increase the herd immunity by improve the sanitation and farm management.